Uncontrolled Hypertension and its Contributing Factors in a Tertiary Care Hospital of Lahore, Pakistan. - Sabir, Omer; Rashid, Anam; Riaz, Muhammad Mohsin (Pakistan Journal of Kidney Diseases, 2021)
Abstract: Hypertension is a major cause of morbidity and mortality worldwide. In spite of the availability of adequate medical therapy, more than half of the patients have blood pressures persistently above the treatment threshold (140/90 mmHg). Objective: To investigate the factors responsible for uncontrolled hypertension. Materials and Methods: It was a descriptive cross-sectional study. The study population comprised of 152 consecutive hypertensive patients more than 18 years of age presenting to the Nephrology Clinic at Fatima Memorial Hospital during the period of one month (July 2020) were included in this study. The criteria for control was defined as an office BP of less than 140/90 mmHg. Results: 96 patients (63.2%) had controlled blood pressure and 56 patients (36.8%) had uncontrolled blood pressure. Males exhibited uncontrolled BP (59%) more than females. Out of all the factors studied, volume status had a significant effect on control of HTN (p=0.003). Conclusion Control of hypertension in our population is still far being perfect. There is a need to fortify our efforts to control hypertension so as to reduce associated morbidity and mortality. At the same time there is a need to conduct large studies to fully elucidate the factors contributing to uncontrolled hypertension in our population.